2004
DOI: 10.1016/j.asr.2003.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Chandra observations of two pulsars PSR 0628-28 and PSR 1813-36

Abstract: PSR 0628-28 is an X-ray emitting radio pulsar which was observed with Advanced CCD Imaging Spectrometer (ACIS) on board Chandra on 2001 November 04 and on 2002 March 25 for 2000 s and 17000 s, respectively. The source countrate was 0.0111±0.0013cps. Making PSR 0628-28 to be the longest period X-ray emitting pulsar. The spectral distribution of counts can be described by several model fits. A blackbody fit yields a temperature kT = 2.69

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The 2.8-Myr-old pulsar B0628-28 is the most puzzling object of this group because it was found to be extremely luminous in the X-ray domain ( Ögelman & Tepedelenlioǧlu 2004). Our analysis of the 20-ks ACIS data of 2001 November shows that the source spectrum is best fitted with a PL model of Γ = 2.73, which is surprisingly steep for a spin-powered pulsar.…”
Section: X-rays From Other Old Pulsarsmentioning
confidence: 74%
See 2 more Smart Citations
“…The 2.8-Myr-old pulsar B0628-28 is the most puzzling object of this group because it was found to be extremely luminous in the X-ray domain ( Ögelman & Tepedelenlioǧlu 2004). Our analysis of the 20-ks ACIS data of 2001 November shows that the source spectrum is best fitted with a PL model of Γ = 2.73, which is surprisingly steep for a spin-powered pulsar.…”
Section: X-rays From Other Old Pulsarsmentioning
confidence: 74%
“…Another 3-Myr-old pulsar, B1813-36, was not detected in a 30 ks Chandra ACIS exposure of 2001 October ( Ögelman & Tepedelenlioǧlu 2004). An upper limit on its X-ray efficiency, η nonth 2−10 keV < 4.4 × 10 −4 , is a factor of 2.5 lower than that for PSR B0950+08.…”
Section: X-rays From Other Old Pulsarsmentioning
confidence: 96%
See 1 more Smart Citation
“…In Table 2 Camilo et al (2004) suggested that PSR J1016À5857 is too faint to be resolved from its background PWN in the Chandra observation, and Hessels et al (2004) found that the spectrum of PSR J2021+3651 can be fit by a BB model and is thus dominated by thermal components. On the other hand, 5 out of the 27 RPP samples in Table 1 are not listed in Table 2 for PWNe, because 5 pulsars have no PWN reported: B0628À28, B0656+14, B0823+26, B0950+08, and B1055À52 (Ö gelman & Tepedelenlioǧlu 2004;Becker et al 2004;De Luca et al 2005).…”
Section: Sample and Data Processingmentioning
confidence: 99%